THE EFFECTIVENESS OF THE ARABIC LANGUAGE COURSE PROGRAM IN IMPROVING THE SPEAKING SKILLS OF STUDENTS AT AL-LATHIFIYYAH 2 ISLAMIC BOARDING SCHOOL - Hidayatul Sholikah; Aufia Aisa; Rina Dian Rahmawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to determine the implementation and role of Arabic language courses in improving the speaking skills of 12th-grade students at the Al-Lathifiyyah 2 Islamic Boarding School in Tambakberas, Jombang. This is a quantitative study. The population of this study consists of 30 students at the Al-Lathifiyyah 2 Islamic Boarding School in Tambakberas, Jombang. The sample in this study was selected using a saturation sampling technique, in which all members were used as the sample. The data collection techniques in this study utilized a quantitative approach involving a closed-ended Likert-scale questionnaire, observation, test instruments in the form of pre-tests and post-tests, and documentation. The results of this study indicate that statistical analysis of the questionnaire and test instruments shows that the percentage of the design and implementation of Arabic language courses in improving the speaking skills of students falls into the “Effective” category. The results of the hypothesis test show that the influence of Arabic language courses on the improvement of Arabic speaking skills at the Al-Lathifiyyah 2 Islamic Boarding School in Tambakberas, Jombang, with a t-value of <0.05 and a significance level of <0.0001. Thus, a value of <0.05 indicates that variable X (effectiveness of the Arabic language course) influences variable Y (speaking skills).